PSYCHOLOGICAL SAFETY AND ITS RELATIONSHIP WITH AGGRESSIVE BEHAVIOR IN A SAMPLE OF PRIMARY STAGE PUPILS IN JEDDAH - Al- Yamani, Kheryah Hassan jaber (Journal of Educational and Psychological Sciences, 2020)
This study aims to investigate the relationship between psychological security and aggressive behavior inside the primary schools for girls in Jeddah. The study dealt with sample of different age groups of primary school children fifth and sixth grade. The sample of the study consisted of 200 from fifth grade and 100 students from sixth grade specifically selected from the student living with their parents as well as randomly selected from different schools in Jeddah. Their ages are between (11- 12) years old. The researcher used the Psychological Security Scale prepared by Mikhimar (2003) and Aggressive Behavior Scale prepared by Amal bada (1991). Method used the study based on descriptive- correlational research design to study the type of relationship between psychological security and aggressive behavior. Results showed the following: • It was found that the strongest inverse association between psychological security scale and aggressive behavior scale across all two- student samples if when one increases the other decreases or as one decreases the other increases. • There was no significant relationship between needs for psychological security and levels of study. The results showed that، the students from fifth grade and sixth grade have the same need for psychological security. • Researcher has found no link between students’ study levels and aggressive behavior scale. Both the students from fifth grade and sixth grade have the same of aggressive behavior scale.